School garden as a learning alternative in the era of COVID-19 pandemic - Okti Purwaningsih; Puguh Bintang Pamungkas; Triwahana Triwahana (University of Merdeka Malang, 2021)
Indonesia as an agrarian country faces several obstacles to achieving food sovereignty, due to the limited number of the younger generation involved in the agricultural sector. Most of the farmers are elderly with limited capacity. Therefore, as early as possible, it is necessary to make efforts to increase interest in farming among elementary school students through School Garden activities. The introduction of the School Garden becomes an interesting lesson because students can carry out farming activities independently. This community service program was carried out at SD Model located in Ngemplak, Sleman, Yogyakarta. This program aims to introduce the School Garden through urban farming so that it can foster interest in agriculture. The methods used include presentations with video tutorials and giving farming modules. The results of the implementation of the community service program showed that 97.7% of students liked the introduction of the School Garden activity and 81.4% of students felt that these activities foster their interest in agriculture.